Military-Industrial Complex on Indonesian Defense Industry Cooperation – South Korea to Support The Defense Economy - R Djoko Andreas Navalino (Budapest International Research and Critics University, 2022)
The approval of the discussion of the Draft Bill on Defense Cooperation between Indonesia and South Korea to become a Law at the DPR RI Plenary Meeting is a new chapter for the sustainability of the joint development program of KFX / IFX fighter aircraft. The government's policy for cooperation with South Korea in the defense industry is centered on developing the Changbogo class submarine and developing the KFX / IFX fighter aircraft. The joint development of the KFX / IFX and Chanbogo Class programs is the first project to master combat aircraft and submarine technology to achieve independence for the Indonesian defense industry. This collaboration shows the potential and challenges that domestic industrial companies must make to support the independence of the defense industry. The research objective is to provide input to the government about the potential and challenges of Defense Industry cooperation in cooperation with South Korea. This research uses qualitative methods to understand social phenomena from the participants' perspectives. The results achieved are by the economic-political view of the Military-Industrial Complex to demonstrate an effective and efficient defense acquisition process.